Thermal performance of Lithium-Ion battery pack using forced air circulation system. (2021) - Bibin, Chidambaranathan; Devan, P.K.; Senthil Kumar, S.; Gopinath, S.; Sheeja, R.; Kanthavelkumaran, N.; Gobinath, S.; Ashok, K.G.
Abstract: The lithium-ion battery broadly used in electric vehicle technology because of its high specific energy and energy density. The major drawback of lithium-ion battery is heat dissipation during charging, discharging and working condition. Due to this heating effect, battery life span decreases, and even battery degradation occurs battery explosion. The battery thermal management system minimises the heat and maintains the battery safely to avoid this problem. There are several Approaches for Battery. In this paper, dual potential battery thermal analysis using CFD to determine the battery thermal behaviour and forced air circulation over the surface of the battery. Finally, temperature contour, electrical parameter graph and Temperature graph concerning flow time after cooling. Therefore, the battery temperature is reduced with forced air cooling and it is examined by the CFD technique.